Exploring language in a multilingual context variation, interaction and ideology in language documentation - Migge, Bettina (Cambridge University Press, 2013)
"Proposing a new methodological approach to documenting languages spoken in multilingual societies, this book retraces the investigation of one unique linguistic space, the Creole varieties called Takitaki in multilingual French Guiana. It illustrates how interactional sociolinguistic, anthropological linguistic, discourse analytical and quantitative sociolinguistic approaches can be integrated with structural approaches to language in order to systematically resolve rarely discussed questions that frequently crop up in projects of language documentation in multilingual contexts. The authors argue that comprehensively documenting complex linguistic phenomena requires taking into account the views of all local social actors (native and non-native speakers, institutions, linguists, non-speakers etc.), applying a range of complementary data collection and analysis methods and putting issues of ideology, variation, language contact and interaction centre stage. This book will be welcomed by researchers in sociolinguistics, linguistic anthropology, linguistic fieldwork and language variation and change"--